2004
DOI: 10.1007/s00204-003-0538-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD) on maternal immune response during pregnancy

Abstract: Whether pregnancy-induced immunosuppression when combined with exposure to 2,3,7,8-tetrachlorodibenzo- p-dioxin (TCDD) could exacerbate immunotoxicity has not been previously investigated. The current study evaluated the immune status of C57BL/6 pregnant and virgin mice following exposure to TCDD. To this end, syngeneically pregnant or virgin female mice were injected intraperitoneally with 10 micro g/kg TCDD. Pregnancy alone significantly decreased thymic cellularity and J11d expression as well as induced cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Our laboratory has previously shown that Fas/FasL-mediated apoptosis constitutes one of the key mechanisms responsible for TCDD-induced killing of T cells and immunotoxicity (Rhile et al, 1996;Kamath et al, 1997Kamath et al, , 1998Kamath et al, , 1999Camacho et al, 2001Camacho et al, , 2002Camacho et al, , 2004aCamacho et al, ,b, 2005Fisher et al, 2004). We have also demonstrated that C57BL/6 mice carrying mutations in Fas and FasL were more resistant to TCDD-mediated thymic atrophy at concentrations of Ͻ50 g/kg body weight (Rhile et al, 1996;Kamath et al, 1999;Camacho et al, 2002Camacho et al, , 2005.…”
Section: Discussionmentioning
confidence: 48%
“…Our laboratory has previously shown that Fas/FasL-mediated apoptosis constitutes one of the key mechanisms responsible for TCDD-induced killing of T cells and immunotoxicity (Rhile et al, 1996;Kamath et al, 1997Kamath et al, , 1998Kamath et al, , 1999Camacho et al, 2001Camacho et al, , 2002Camacho et al, , 2004aCamacho et al, ,b, 2005Fisher et al, 2004). We have also demonstrated that C57BL/6 mice carrying mutations in Fas and FasL were more resistant to TCDD-mediated thymic atrophy at concentrations of Ͻ50 g/kg body weight (Rhile et al, 1996;Kamath et al, 1999;Camacho et al, 2002Camacho et al, , 2005.…”
Section: Discussionmentioning
confidence: 48%
“…On days 2 (GD 16) and 4 (GD 18) after DES treatment, thymic cellularity of both mothers and fetuses was determined. We had shown previously that pregnant mice exhibit a dramatic decrease in thymic cellularity compared with nonpregnant mice, and exposure to environmental contaminants, such as TCDD, further decreases their numbers (Camacho et al, 2004a). We noted that, unlike nonpregnant mice that showed ϳ250 million thymocytes/mouse (Camacho et al, 2004a), pregnant mice on GD 16 had fewer than ϳ11 million cells/mouse.…”
Section: Des Induces Alterations In Thymic Cellularity In Pregnant MImentioning
confidence: 80%
“…Thymocytes from mice exposed to DES or VEH were analyzed for apoptosis by using the TUNEL assay kit (Roche Diagnostics, Indianapolis, IN) as described previously (Camacho et al, 2004a(Camacho et al, ,b, 2005Singh et al, 2008). In brief, thymocytes (1 ϫ 10 6 ) from various groups of mice were cultured for 24 h in complete RPMI 1640 medium.…”
Section: Methodsmentioning
confidence: 99%
“…This raises an important question as to why TCDD can suppress T-cell response to an antigen in vivo, whereas it is not directly toxic to T cells in vitro. Recent studies from our laboratory shed some light in this regard by demonstrating that TCDD-induced apoptosis in thymic T cells is dependent on their interactions with thymus stromal cells (Camacho et al, 2004a(Camacho et al, ,b, 2005. We have demonstrated previously that in vivo administration of TCDD leads to up-regulation of Fas on T cells and FasL on thymic stromal cells and that interaction between these cells is critical for T cells to undergo apoptosis (Camacho et al, 2005).…”
Section: Role Of Dendritic Cells In Tcdd-induced T-cell Apoptosismentioning
confidence: 99%